Penerapan Decision Tree untuk Prediksi Kepuasan Pengguna Bus Transjakarta - Reza Hikmatulloh; Hanna Mahaerani Putri; Qurrotul Aini (Innovation in Research of Informatics (INNOVATICS), 2020)
Transjakarta buses are one of the public transportation facilities used by residents of the capital city of Jakarta. The existence of Transjakarta Buses, transportation access is easier and easier for its users. With so many users, there are several things that must be considered in the facilities and infrastructure provided by the Transjakarta Bus. User satisfaction is an assessment given by a user of a service, whether satisfied or not. This research was conducted to analyze the satisfaction of Transjakarta Bus users who are students of Syarif Hidayatullah State Islamic University Jakarta. The attributes to be taken in the study include the rates, facilities, and services provided by the Transjakarta Bus where the questionnaire results will be processed using the C4.5 Decision Tree method. The results showed that an accuracy of 92.86% was obtained with accuracy in Good Classification using Confusion Matrix.